Emergence of an European innovation system and its impact on Austria - Klaus Schuch (European Regional Science Association (ERSA), 1998)
The concept of a European Innovation System (EIS), defined as common effort of the EU as a whole and not merely as sum on national undertakings of the EU member states, has never been far below the surface for those seeking to create a united Europe. However, it needed a lot of years to emerge on the surface, still these days mor an - partly already operationalised - idea than an elaborated conceptual policy. In a brief historical perspective the emergence of the EIS wil be elaborated. At the time being, the 4th Framework Programme for European RTD (FP4) is running. It covers the period from 1994 until 1998 and encompasses an overall budget of approx. 15 billion ECU, which is considerably higher than the respective budgets in the late 1980s. However, the budget for FP4 and FP5 as well is still just around 4 % of the sum of all national public RTD-budgets of the 15 member states. Moreover, in terms of R&D expenditure, the EU is still lacking behind its main global competitors. While there is a slight but steady decreasing trend in those EU countries which already spend the largest proportion on R&D expenditure, most growth can be stated either in those countries starting from a relatively low base or the Nordic countries, while the Austrian value stagnates. The differences in the distribution of R&D expenditures by socio-economic objectives between the various national governments and the European Commission are remarkable. The objectives laid down in FP4 can be regarded as an additional value for the Austrian innovation system. Due to its specific nature, FP4 has some substantial advantages for the Austrian innovation system.First, Austria contributes roughly three per cent of the total FP4 budget, but has access to considerably more know-how. Second, the EU RTD programme is based on inter-institutional networking. This forces and facilitates the entry of industrial enterprises in research consortia and thus stimulates the co-operation between academic and enrepreneurial research efforts. Third, there are a lot of EU RTD efforts which focus directly on the active participation of SMEs, which form the overall industrial structure in Austria. The fourth advantage of the EU RTD programmes for Austria lies in its obvious and highly necessary concentration on high-tech sectors. In Austria the rate of export specialisation on goods with high R&D-input is twice as low as in the EU. First results of the Austrian participation in FP4 show some remarkable features. Out of 3972 submitted project proposals with Austrian participation, 1053 were funded by the EC. Especially successful were proposals with Austrian participants from the business sector (40 % of successful proposers), followed by participants from the universities (32 %) and non-university research institutions (16 %), both below their respective share in terms of application. Concerning the different technological programmes, Austria performed especially well in the non-nuclear energy programmes, in some of the environmental targeted research programmes, in information technologies and telematics as well as in transport targeted research.
Keywords: 330